A simple intervention improves the recording of vital signs in children presenting to the emergency department. Issue 10 (22nd September 2009) - Bird, C; Shea, A; Michie, C A; George, G
Abstract : Objectives: Vital signs are often not documented in paediatric patients at triage. This study was conducted to find out whether the use of a small, laminated aide memoire and a short teaching session might improve this situation. Methods: A preliminary audit of the measurement of vital signs in 106 children aged less than 6 years was carried out in a district general hospital emergency department (ED). A small card illustrating normal values for these was then distributed—this could be attached to staff identity cards. At the same time doctors and nursing staff were given a teaching session on the importance of these measures. The audit was then repeated in a further 106 children. Results: There was significant improvement in recording of all vital signs with the exception of blood pressure and temperature. Conclusion: A low-cost card together with a short period of training offers a useful strategy to improve the rate of documentation of vital signs in children presenting to the ED.